Spatial distribution of hotspots in Peninsular Malaysia - Nuruddin, Ahmad Ainuddin; Abd Halim, Nur Shuhada; Mohd Razali, Sheriza (2010)
This study was conducted to quantify number of hotspots and develop maps of hotspots occurrence using Geographic Information System (GIS). The study covered five years period starting from 2003 until 2007. Secondary data of hotspots in Peninsular Malaysia were obtained from NOAA-12 satellite, provided by MACRES. The results showed a total of 3503 hotspots over five years with 2005 contributed to the highest amount. The results also showed that comparatively, February ranked as the highest hotspots number, followed by March and January; due to burning activities of agriculture waste and dry fuels available at that time. This study concluded that hotspots pattern in Peninsular Malaysia was highest in 2005 while highest monthly hotspots occurrence was in February.